Les piliers méthodologiques du SCN 2008 - Mohammed Tahar DEROUICHE (Revue des Sciences Humaines)
Algeria plans to adopt a system of national accounts 2008 SCN from the year 2014. this article would explain the methodological pillars on which to base the system of national accounts reference, to see the importance of preparing management structures (institutional, technological, human...) Appropriate, which should be available by Algeria to the success of this process, which undoubtedly require a lot of effort at all levels.